EFFORTS TO INCREASE STUDENTS SELF-EFFICACY IN MATHEMATIC SUBJECT WITH FLAT SHAPE MATERIAL THROUGH A PROBLEM BASED LEARNING MODEL - Banindra Yudha, Chrisnaji; Nurmulia Diniarti; Satria Indra Kusuma (Media Inovasi Pendidikan dan Publikasi, 2023)
This research purpose to increase students' self-efficacy in mathematics subjects with flat material through the problem based learning model at SDN Pisangan Timur 05 Pagi Jakarta Timur. This Classroom Action Research was carried out in 3 cycles, where each cycle contained 4 stages including: a.) Planning, b.) Acting, c.) Observing, and d.) Reflecting. The research results show that there is an increase in learning outcomes which can be seen from the implementation of research in each cycle. Self efficacy can be seen from the score obtained before the class average was 49.94% in the low category, in cycle I it increased to 69.2% in the medium category, and in cycle II it increased to 85.04% in the very high category. The increase in student self-efficacy can be seen from the majority of students being able to solve problems given by the teacher through teaching aids, students do not hesitate to work on problems with group members, students are able to think independently when solving mathematical problems, students are confident in the solution and dare to give opinions regarding differences problem solving, students have the ability and confidence in the correctness of concepts, principles of mathematical procedures regarding the problem being solved.